Poisson theory of elastic plates select proceedings of IPDIMS 2020 - Vijayakumar, Kaza; Ramaiah, Girish Kumar (Singapore Springer, 2021)
This groundbreaking book resolves the main lacuna in Kirchhoff theory of bending of plates in the Poisson-Kirchhoff boundary conditions paradox through the introduction of auxiliary problem governing transverse stresses. The book highlights new primary bending problem which is formulated and analyzed by the application of developed Poisson theory. Analysis with prescribed transverse stresses along faces of the plate, neglected in most reported theories, is presented with an additional term in displacements. The book presents a systematic procedure for the analysis of unsymmetrical laminates. This volume will be a useful reference for students, practicing engineers as well as researchers in applied mechanics.
Electronic reproduction
Keywords: Plates (Engineering); Flexure; Elastic plates and shells -- Mathematical models; Electronic books